Non-HDL-C and age-stratified mortality risk in the US general population: a population-based cohort study - Fu, Zhiqing; Zhang, Wei; Li, Shan (Frontiers in Nutrition, 2025)
IntroductionNon-high-density lipoprotein cholesterol (non-HDL-C) is a well-established residual causal risk factor for the progression of atherosclerotic cardiovascular disease. However, studies of large, broadly generalizable populations are lacking, and the effect of non-HDL-C on all-cause and cause-specific mortality, particularly in different age groups, remains uncertain.MethodsWe conducted a population-based cohort study using data from the National Health and Nutrition Examination Survey from 1999 to 2018. Participants were divided into six groups according to non-HDL-C levels (≤100, 101–130, 131–160, 161–190, 191–220, >220 mg/dL). Multivariable Cox proportional hazards models were used to calculate hazard ratios (HR) and corresponding 95% confidence intervals (CI). Restricted cubic spline curves and subgroup analysis were also performed to further explore the association between non-HDL-C and mortality.ResultsOf 51,252 individuals (mean age 48.1 ± 19.2 years), 7,605 (14.8%) died during follow-up. Both low and high non-HDL-C levels were significantly associated with increased risk of all-cause and cause-specific mortality, suggesting a U-shaped association. Thresholds of 156, 142, 162, and 152 mg/dL were identified for all-cause, cardiovascular, cancer, and other-cause mortality, respectively. We observed significant interactions between non-HDL-C and age for all-cause and cardiovascular mortality (P interaction<0.05 for each). The association of high non-HDL-C (>220 mg/dL) with all-cause and cardiovascular mortality was strongest in adults aged <50 years (HR, 1.51 [1.09–2.08] and 1.97 [1.07–3.12], respectively), intermediate in adults aged 50 to 69 years, and weakest in adults aged ≥70 years.ConclusionNon-HDL-C was U-shaped associated with all-cause and cause-specific mortality in the US general population. However, in younger adults (<50 years), the higher the non-HDL-C, the higher the risk of cardiovascular and all-cause mortality. These observations support clear public health messaging and strict adherence to primary prevention strategies for atherosclerosis in younger adults. This has important implications for the development of age-specific interventions to reduce mortality associated with non-HDL-C levels.